Saprolegnia sp. (Fungi: Saprolegniaceae) isolation from Onchorhyncus mykiss (Pisces: Salmonidae) “rainbow trout” culture - Alzamora, Libertad (1999)
The objective of the study was to determine the infectious origin of the alevines mortality and lesions observed in adults of Oncorhynchus mykiss Walbaum 1792, "rainbow trout", in the fishfarm "El Ingenio" using a simple and effective methodology. Alevines, eggs and adult forms and samples of water from ponds were collected. These samples were cultivated on seeds of Cucurbita maxima "calabash" as substrate, where typical colonies had been developing alter seven days. Microscopic characteristics of the hyphae fitted the graphic pattern of Saprolegnia sp. (fungi), which is related to the symptomatology observed in the captured adults. The presence of Saprolegnia sp. would be related to high mortality of alevines registered (40%), probably for importation of eggs contaminated with the fungi. The method was efficient because the substrate has permitted the development 01 the fungi for an easy and cheaply application.